A RANDOMIZED PROSPECTIVE COMPARATIVE STUDY TO ASSESS THE EFFICACY OF CONCURRENT CHEMORADIATION WITH ERLOTINIB VERSUS CISPLATIN IN LOCALLY ADVANCED HEAD AND NECK CANCER PATIENTS - Dr Ramesh Arya; Dr Manish Verma; Dr Karuna Abgad; Dr Aishwarya Sharma (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Non-communicable diseases (NCDs) are responsible for the major proportion of mortality worldwide with cancer projected to be the leading cause of death and the single critical barrier to increasing life expectancy globally.  (1)Head and neck cancer (HNC), ranking as the seventh most common cancer globally, encompasses a diverse array of tumours affecting the upper aero digestive tract. Head and neck squamous cell carcinoma (HNSCC) is a group of malignancies originating from the squamous cells lining the tissues of the head and neck region, including the oral cavity, hypo pharynx, nasopharynx, oropharynx, lip, nasal cavity, paranasal sinuses, and salivary glands .HNSCC is a major global health concern, displaying variable incidence and mortality rates across different geographic areas and demographic characteristics.. (2)